2012
DOI: 10.4172/2155-6156.1000227
|View full text |Cite
|
Sign up to set email alerts
|

Association of Common Variants of CDKN2A/2B Rs10811661 (C/T)and WFS1 Rs6446482 (C/G) to Type 2 Diabetes Mellitus in the Indian Population of Eastern Uttar Pradesh

Abstract: Aim: Recent genome-wide association studies (GWAS) have identified several unsuspected genes that significantly increase the risk of type 2 diabetes mellitus (T2DM). We aimed to replicate the association of a common variant each in CDKN2A/2B (rs10811661) and WFS1 (rs6446482) in the population of Eastern Uttar Pradesh, India. These variants have been identified to be differentially associated with T2DM in different ethnic groups in previous GWAS. Results:We found SNP rs10811661 of CDKN2A/2B (OR 1.50, 95% CI 1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Although another study constituting samples from northern and western India 4 showed strong association of CDKAL1 with T2DM, the single SNP studied was different from those of the present study. The rs10811661 of CDKN2A/B also showed strong association with T2DM in our population as was the case with north and western Indian studies 4 5 . However, the variant near HHEX gene (rs1111875) was not significantly associated with T2DM in our study similar to other Indian populations studied 2 3 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although another study constituting samples from northern and western India 4 showed strong association of CDKAL1 with T2DM, the single SNP studied was different from those of the present study. The rs10811661 of CDKN2A/B also showed strong association with T2DM in our population as was the case with north and western Indian studies 4 5 . However, the variant near HHEX gene (rs1111875) was not significantly associated with T2DM in our study similar to other Indian populations studied 2 3 .…”
Section: Discussionsupporting
confidence: 83%
“…Comparison with earlier studies among Indian populations : Despite unique Indian population structure with large number of endogamous groups and enormous ethnic, linguistic and geographic heterogeneity, very few studies have hitherto focused on replication of earlier findings of genetic association of T2DM 2 3 4 5 . The risk allele frequencies of all the SNPs considered in our study were compared with other Indian studies ( Table IV ).…”
Section: Resultsmentioning
confidence: 86%
“…Chauhan et al [89] have replicated association of eight well established genetic variants with T2D in north-western Indian populations showing higher effect size compared to the Europeans. We have also shown higher effect size compared to European populations of two of the well established genetic variants in eastern Uttar Pradesh population of India [91].…”
Section: Current Status In Indian Populationmentioning
confidence: 81%
“…Genotyping of the FTO polymorphism was carried out using allele-specific PCR. Primers, enzymes, and reaction conditions for the rest of the SNPs were as previously reported [15][16][17][18][19][20][21][22][23]32]. Sequences of the PCR primers employed in this work are presented in Table 3.…”
Section: Issn: 2475-5591mentioning
confidence: 99%